Simulated and experimental validation of a fuel cell-supercapacitor passive hybrid system for electric vehicles - Wu,B; Yufit,V; Campbell,J; Offer,GJ; Martinez-Botas,RF; Brandon,NP (Iet Conference Publications, 2013)
The concept of a fuel cell-supercapacitor hybrid system involves the direct coupling of the two devices to achieve the same benefits of hybridisation but without the need for costly DCDC converters. Using an experimentally validated steady state fuel cell model and a transmission line based supercapacitor model, it has been shown that the passive hybridisation allows for efficiency gains of approximately 16% compared to a pure fuel cell system. Under load, the supercapacitors meets the peak power requirement due to their lower impedance giving the FC time to ramp up. Under no load conditions, the fuel cell gradually charges the supercapacitors back to the steady state thermodynamic equilibrium potential. A fast fourier transform analysis of the respective loads under an automotive drive cycle showed that the supercapacitors act as a low pass filter, reducing the magnitude of load oscillations from the fuel cell. This therefore addresses two of the main modes of fuel cell degradation in automotive applications: rapid power cycling and no load idling.